Unusual evolution from a superconducting to an antiferromagnetic ground state in Y1-xGdxPb3 (0 ≤ x ≤ 1) UNUSUAL EVOLUTION from A SUPERCONDUCTING to ⋯ M. CABRERA-BAEZ et al. - Cabrera-Baez, M.; Denis, V. C.; Mendonça-Ferreira, L.; Carlone, M. [UNESP]; Venegas, P. A. [UNESP]; Avila, M. A.; Rettori, C. (American Physical Society (APS), 2018)
We have studied the evolution of Y1-xGdxPb3 (0≤x≤1) from its superconducting (x=0) to antiferromagnetic (x=1) states with critical temperatures Tc=4.6(2)K and TN=15.7(2)K, respectively. At relatively low Gd concentrations (x≤0.03) Tc presents a weak but linear suppression with increasing x, as expected from the Abrikosov-Gorkov (AG) theory describing the Cooper pair breaking due to the exchange interaction between the impurity localized magnetic moment and the conduction electrons (ce). This linear Tc suppression rate leads to an effective exchange parameter of (J2(q))AG1/2=0.20(7)meV between the 4f localized electrons and the ce. For intermediate Gd concentrations (0.03≤x≤0.15), although no Gd clustering is observed, there is an unusual inflection and leveling off trend in Tc, indicating that the superconducting phase persists until the highest Gd concentration in this region where magnetic interactions are evidenced by increasingly negative values of the Curie-Weiss temperature ΘC. Analysis of low-TGd3+ electron spin resonance (ESR) experiments and their ESR line-shape simulations, in conjunction with the trend in Tc, leads us to suggest that an exchange bottleneck mechanism between the Gd+3 localized magnetic moment and the ce may be the reason behind the inhibition of the Cooper pair-breaking mechanism, in favor of a magnetic interaction via ce polarization. Therefore, our superconducting and ESR results suggest a scenario where superconducting and magnetic phases coexist extensively in the Y1-xGdxPb3 system, mediated by different types of ce.